2019
DOI: 10.1186/s13256-019-2039-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric symptoms in a patient with Dyke–Davidoff–Masson syndrome and systemic lupus erythematosus: a case report

Abstract: Background Dyke–Davidoff–Masson syndrome is an uncommon constellation of radiological and clinical findings. Few reports describe co-occurring psychiatric manifestations. Systemic lupus erythematosus is a systemic disease with vascular, neurologic, and psychiatric involvement. To the best of our knowledge, no case reports have been made associating these entities. Case presentation We present the case of a 21-year-old Mexican mestizo woman with a history of systemic lup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…SLE could present with other autoimmune disorder as well, which could possibly complicate the treatment. The study conducted by Sordia-Ramírez et al showed the presence of neuropsychiatric symptoms in a patient with Dyke-Davidoff-Masson syndrome [14]. The seizures in this patient presented due to cortical hypotrophy in the left medial temporal lobe.…”
Section: Discussionmentioning
confidence: 61%
“…SLE could present with other autoimmune disorder as well, which could possibly complicate the treatment. The study conducted by Sordia-Ramírez et al showed the presence of neuropsychiatric symptoms in a patient with Dyke-Davidoff-Masson syndrome [14]. The seizures in this patient presented due to cortical hypotrophy in the left medial temporal lobe.…”
Section: Discussionmentioning
confidence: 61%
“…The characterization of neuropsychiatric manifestations of DDMS was one of the main contributions of this study. Very few DDMS cases complicated by psychiatric manifestations in DDMS were reported [ 7 12 ]. The involvement psychiatric disorders including schizophrenia, schizoaffective disorder, bipolar I mania, depressive episode and emotional dysregulation have been reported in patients with DDMS [ 7 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very few DDMS cases complicated by psychiatric manifestations in DDMS were reported [ 7 12 ]. The involvement psychiatric disorders including schizophrenia, schizoaffective disorder, bipolar I mania, depressive episode and emotional dysregulation have been reported in patients with DDMS [ 7 12 ]. Intellectual disability, depressive symptoms, suicidal ideation and behavioral symptoms were documented in a 21-year-old woman with a history of systemic lupus erythematosus [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations